Business Cycle Synchronization Between CEE Countries and Euro Zone - Piłat, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The main aim of the article is to estimate the level of business cycles synchronization between Central and Eastern European Countries (CCECs) and euro area. Similarity of business fluctuations is a main factor that can define if common monetary policy conducted by European Central Bank is effective, i.e. is able to mitigate economic fluctuations in all countries that adopted euro. The level of business cycle synchronization was analyzed on the basis of different morphological features of business fluctuations: phase length, amplitude magnitude and phase shifts. Results show that, among analyzed countries, business cycles of Czech Republic, Croatia and Poland are at the highest level synchronized with fluctuations in euro area. Hungary business cycle is less synchronized especially as far as the length of cycle phase is concerned. The most diverged business cycle in comparison to fluctuations in euro is Romanian cycle.